Motivators and barriers for dog and cat owners and veterinary surgeons in the United Kingdom to using preventative medicines - Belshaw, Zoe; Robinson, Natalie J.; Dean, Rachel S.; Brennan, Marnie L. (Elsevier, 2018)
Routine use of preventative medicines is advocated as part of responsible dog and cat ownership. However, it has been suggested that the number of owners in the United Kingdom (UK) using preventative medicines to protect their pets is in decline. The aim of this novel study was to use a qualitative methodology to explore the attitudes of pet owners and veterinary surgeons in the UK to using preventative medicine products in dogs and cats. Preventative medicine was defined as “a drug or any other preparation used to prevent disease, illness or injury.” Semi-structured interviews were conducted by telephone with owners and veterinary surgeons who had recently participated in a preventative healthcare consultation. Thematic analysis of transcribed recordings of these interviews identified four themes. This paper reports the theme related to motivators and barriers to using preventative medicines. Owners’ understanding varied widely about the importance of preventative medicines for pets, as did their confidence in the safety of prescription products. A good relationship with their veterinary surgeon or practice, seeing adverts on the television about specific diseases, advice from a breeder and having personally seen infected animals appeared to be motivators for owners to use preventative medicines. Concern about adverse events and uncertainty about the necessity of using preventative medicines were barriers. Owners who trusted their veterinary surgeons to advise them on preventative medicine products described little use of alternative information sources when making preventative medicine choices. However, owners who preferred to do their own research described reading online opinions, particular in relation to the safety of preventative medicines, which they found confusing. In contrast, veterinary surgeons described broad confidence in the safety and efficacy of prescription preventative medicines and described protection of pet health as a strong motivator for their use. Several expressed some concern about being seen to “sell” products, which may present a barrier to their advocacy. Veterinary surgeons were unsure about owners’ level of understanding of the necessity of preventative medicines, particularly in relation to vaccinations, and few recalled instigating conversations with owners about product safety. Owner uncertainties about preventative medicine products may not be adequately addressed in the consulting room. This first qualitative study to investigate dog and cat preventative medicines suggests strategies are needed to increase discussion between pet owners and veterinary surgeons in the UK about the necessity, safety, efficacy and cost of preventative medicines.